The Role Of Technological Poles In Knowledge Production - Ben Mazouz ,Hichem; Kermani ,Houda (جامعة الوادي University of Eloued, 2025)
This research paper aims to shed light on the role of technological poles in knowledge production, by studying the Sidi Abdellah technological pole and its role in knowledge production in Algeria. The components of technological poles and their importance in supporting scientific research and innovation were reviewed. We also focused on the role of educational and research institutions associated with this pole, in addition to local and international partnerships that contribute to enhancing knowledge production . We used the descriptive analytical approach to collect and analyze data from previous literature and relevant reports, with the aim of providing a clear picture of the extent of the contribution of the Sidi Abdellah technological pole to knowledge production. It was concluded that knowledge production in this pole depends mainly on higher schools that play a pivotal role in generating knowledge in addition to partnerships and research cooperation.
The role of technological poles in knowledge production: Sidi Abdellah technological pole as a model in Algeria
Keywords: technological poles; knowledge production; Sidi Abdellah technological pole in Algeria